Great Power Politics and United States' Withdrawal from Afghanistan - Wardoyo, Broto (Global Strategis, 2024)
On October 7, 2002, the United States (US) started their military operation in Afghanistan to seek Osama bin Laden, the leader of Al Qaeda (AQ) who was responsible for the September 11, 2001, terror attacks commonly referred to as the 9/11 attacks. US military operations in Afghanistan, however, remained active after Osama bin Laden was killed. In February 2020, the US signed an agreement with the Taliban, who provided sanctuary for Osama bin Laden and AQ, which practically ended their military operation in Afghanistan. This article seeks to explain why the US decided to sign an agreement with the Taliban even though both AQ and the Taliban are still in operation. This article argues that the US decision to sign the agreement and withdraw from Afghanistan is due to the need to reallocate resources as part of their retrenchment policy. Keywords: Great Power Politics, Retrenchment, Withdrawal, the United States, Afghanistan, Al Qaeda, Taliban Pada tanggal 7 Oktober 2001, Amerika Serikat (AS) memulai operasi militer di Afghanistan untuk mencari Osama bin Laden, pemimpin Al Qaeda (AQ) yang menjadi otak (mastermind) serangan teror 11 September 2001 atau dikenal sebagai serangan 9/11. Meski demikian, operasi militer AS di Afghanistan tidak berhenti setelah Osama bin Laden terbunuh. Operasi militer AS di Afghanistan terus dipertahankan hingga mereka memutuskan mundur dari negara tersebut setelah penandatanganan kesepakatan damai dengan Taliban di Doha pada bulan Februari 2020. Tulisan ini mempertanyakan mengapa AS mundur dari Afghanistan meski tujuan yang ingin mereka sasar di negara tersebut belum tercapai. AQ maupun Taliban, kelompok yang memberikan perlindungan bagi AQ, masih tetap ada dan beroperasi. Tulisan ini berargumen bahwa keputusan AS tersebut terkait dengan adanya kebutuhan untuk mengalihkan alokasi sumber daya sebagai bagian dari kebijakan retrenchment. Kata-kata Kunci: Pertarungan Negara Besar, Retrenchment, Penarikan Mundur, Amerika Serikat, Afghanistan, Al Qaeda, Taliban